Remapping sound studies - Steingo, Gavin; Sykes, Jim, 1976- (Duke University Press, 2019)
Exploring a wide range of sonic practices, from birdsong in the Marshall Islands to Zulu ululation, the contributors reorient the field of sound studies toward the global South in order to rethink and decolonize modes of understanding and listening to sound